The Relationship between Length and Weight and Condition Factors of Lompa Fish (Thryssa baelama) in Kabauw Village Waters - Sangadji, Madehusen; Padang, Anita; Wasahua, Jahra; Kastela, M. Udhafi (Fakultas Pertanian Universitas Darussalam Ambon, 2024)
The biology of the Lompa fish (Thryssa baelama, Forskall, 1975) in the waters of Kabauw Beach, Central Maluku is not yet known. This research aims to analyze fish size, the relationship between length weight and condition factors of Lompa fish. A total of 628 fish samples were collected using cast net fishing gear, from October – November 2023. The results showed that the total length of the fish ranged from 6 – 6.5 cm and body weight ranged from 1,703 – 13,072 grams. The relationship model for the length and weight of male fish W = 0.0102L2.8294 and female fish W = 0.0119L2.7501, and the combination of male and female W = 0.0111L2.7885. The condition factor (K) of male Lompa fish (Thryssa baelama) ranges between 0.695 – 1.3728 (0.993 ± 0.0779) and for females ranges between 0.7912 – 1.3783 (1.0056 ± 0.0807).